2018
DOI: 10.1016/j.jece.2018.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical treatment for the degradation of cyanotoxins with emphasis on drinking water treatment—How far have we come?

Abstract:  Cyanotoxins removal are dependent on environmental parameters, mainly pH and Natural Organic Matters  Chlorination and ozonation employed for cyanotoxin treatment may breach guideline values  Membrane technology and photocatalysis operation involves high energy and maintenance  Specific reaction pathway shifts oxidation process more towards sustainable approach

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 126 publications
1
30
0
1
Order By: Relevance
“…This collateral effect represents an important risk for human health and other ecosystem services, as it is expected that 10-95% of the recorded blooms contain cyanotoxins (Antoniou et al 2005;Sivonen and Jones, 1999). Human exposure to these toxins may occur through ingestion of drinking-water and during recreational use of water bodies with cyanobacterial blooms (He et al, 2016;Stewart et al, 2006;Pantelić et al, 2013;Kumar et al, 2018). A number of episodes of human and animal poisoning by ingestion of cyanotoxins-bearing water have been reported since the late 1800s (Antoniou et al, 2005;Carmichael, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This collateral effect represents an important risk for human health and other ecosystem services, as it is expected that 10-95% of the recorded blooms contain cyanotoxins (Antoniou et al 2005;Sivonen and Jones, 1999). Human exposure to these toxins may occur through ingestion of drinking-water and during recreational use of water bodies with cyanobacterial blooms (He et al, 2016;Stewart et al, 2006;Pantelić et al, 2013;Kumar et al, 2018). A number of episodes of human and animal poisoning by ingestion of cyanotoxins-bearing water have been reported since the late 1800s (Antoniou et al, 2005;Carmichael, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that MC-LR removal lessened in the presence of NOM in the biofilters compared with the nonbioaugmented filter (FC). This can be attributed to the scavenging between the NOMs and the oxidants formed during the oxidation reaction (Kumar et al 2018a), which has been reported to decrease the reaction rate by >50% (Verma and Sillanpää 2015).…”
Section: Mc-lr Analysis and Residual Ozone Determinationmentioning
confidence: 97%
“…Physical and/or chemical treatments (e.g., reverse osmosis, chlorine, and ozone) are effective for removal of MCs, and several are regularly used in drinking water treatment facilities (Kumar et al, 2018). In addition, efforts have been made to develop alternative strategies for MC removal, e.g., the heterologous expression of the MlrA enzyme (Wang et al, 2017; Dexter et al, 2018), bioreactors with immobilized Escherichia coli expressing the MlrA enzyme (Dziga et al, 2014), or inoculated with MC degrading bacteria (Tsuji et al, 2006; Phujomjai et al, 2016; Kumar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%